2016
DOI: 10.21649/akemu.v22i3.1395
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hyperglycemia with In-Hospital Mortality in Septicemia

Abstract: Objective: To document association of hyperglycemia with mortality in septicemic patients. Methods: After approval from departmental review committee, this retrospective comparative study was conducted from the chart review of 197 medical files of patients with primary diagnosis of bacterial sepsis admitted in a medical unit of department of Internal Medicine, King Edward Medical University Lahore from October 2012 to Septfember 2013. Sepsis was defined as by international sepsis definitions conference criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The commonest problem was hyperglycemia in both groups. Afzal et al have also found hyperglycemia to be a common problem in sepsis patients and if remain uncontrolled, can be a cause of increased mortality (3) . There were more cases of organ dysfunction in control group as compared to study group and mortality were higher in patients who developed organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The commonest problem was hyperglycemia in both groups. Afzal et al have also found hyperglycemia to be a common problem in sepsis patients and if remain uncontrolled, can be a cause of increased mortality (3) . There were more cases of organ dysfunction in control group as compared to study group and mortality were higher in patients who developed organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%